Plasma Concentration of Advanced Glycation End-Products From Wild Canids and Domestic Dogs Does Not Change With Age or Across Body Masses - Jimenez, Ana Gabriela (Frontiers in Veterinary Science, 2021)
Dogs provide a physiological paradox: In domestic dogs, small breeds live longer lives than large breed dogs. Comparatively, a wild canid can be a similar size than many large breed dogs and outlive their domestic cousin. We have previously shown that oxidative stress patterns between domestic and wild canids differ, so that wild canids invest in a robust antioxidant system across their lives; whereas domestic dogs tend to accumulate lipid damage with age. There is a close association between oxidative stress and the production of a carbohydrate based-damage, Advanced Glycation End-products (AGEs). AGEs can bind to their receptor (RAGE), which can lead to increases in reactive oxygen species (ROS) production, and decreases in antioxidant capacity. Here, I used plasma from wild and domestic canids to address whether blood plasma AGE-BSA concentration associated with body mass and age in domestic dogs; And whether AGE-BSA concentration patterns in blood plasma from wild canids are similar to those found in domestic dogs. I found no correlation between circulating AGE-BSA concentration and body size or age in either domestic dogs and wild canids. These data suggest that AGEs formation may be a conserved trait across the evolution of domesticated dogs from wild ancestors, in opposition to oxidative stress patterns between these two groups. And, that, in domestic dogs, lipid metabolism, rather than carbohydrate metabolism, may be upregulated to yield the previously found differences in circulating lipid damage across lifespan and body sizes.